Patología tumoral en el Servicio de Otorrinolaringología del Hospital Clínico Universidad de Chile - Valencia P., Felipe; Gutiérrez C., Daniela; Celedón L., Carlos (Revista Hospital Clínico Universidad de Chile, 2011)
The head and neck neoplasm’s are a frequent cause of consultation in ENT (ear, nose and throat) pathologies. For practical purposes, the head and neck cancers can be classified according to their anatomical location, in sinonasal, pharyngeal, laryngeal, oral, otologic and salivary glands. The objective of this work is to give a description of tumoral cervico facial pathology that was seen in the Otolaryngology service of HCUCH (Hospital Clínico Universidad de Chile) in 2010, in order to understand and present the local situation and establish the most common entities. We included 120 patients with diagnosis of tumoral pathology, which yielded the following results: 20.8% of salivary glands, 19.2% of sinonasal, 17.5% of the larynx, 16.7% of Mouth tumors, 9.2% of the pharynx, 8.3% of neck, 2.5% of ear, and 5.8% of others which couldn´t be classified. In our results dominate most common etiologies of head and neck pathology, predominates such as larynx and mouth cancer, and benign tumors of the parotid gland. Some rare entities in the general population appear in higher proportions in this study, because this clinic tends to concentrate these pathologies. On the other hand, there are other low-frequency neoplasms, which didn´t appear in our cases, probably because it was taken in a limited time of 1 year.